A Production and operations management study on Pascual Laboratories, Inc. - Salvatus, Cherrie Joy (College of Engineering, 1999)
Pascual Laboratories, Inc.. is a manufacturing firm that produces a wide range of products that are categorized into: cardiovascular and pulmonary therapy, antiseptics, oral rehydration, health supplements and dermatology. It is known for its high quality since this should be the top most priority of every manufacturing company that is concerned with pharmaceutical products. The study group focused on only one production line which is the Ascof 300mg tablets, a colds and cough herbal medicine, and tackles Production and Operations Management side where a number of problems was detected. The three major problems identified that heed investigation and analysis, high level of raw materials inventory and high manufacturing cost concerned in the production. Several plant visits and interviews with the PPIC manager and plant industrial engineer were made to obtain first hand information that are essential in the analysis of the problem. Different techniques were used to analyze the three problems and find the root causes. These are the Ishikawa diagrams, inventory control, job sequencing, forecasting and materials requirement planning. From the analysis, several recommendations are presented by the group for the improvement of the production and operations system of Ascof 300mg tablets. Such recommendations are made in accordance to inventory control, forecasting, job sequencing and layout.